Georgette Heyer, history, and historical fiction - Rayner, Samantha J.; Wilkins, Kim (UCL Press, 2021)
Georgette Heyer, History, and Historical Fiction brings together an eclectic range of chapters to explore the work and influence of novelist, Georgette Heyer.